Dietary α-galactosidase and xylanase to improve the nutritional value of corn-soybean-rapeseed meal diets in broiler chickens - Alberto Viñado; Saksit Srinongkote; Josep Mascarell; Rene Morales; Javier Estévez; Sergi Carné (Journal of Applied Animal Research)
Two experiments were performed to assess the effects of an enzyme preparation (containing α-galactosidase and xylanase) on chicken performance, carcass traits, footpad dermatitis score, and nutrient digestibility. During first experiment, chickens were fed four diets: (1) control diet (PC): corn and soybean-rapeseed meal; (2) PC supplemented with 350 ppm of the enzyme; (3) Negative control (NC): PC with a 4% reduction of apparent metabolizable energy (AME) and crude protein content; (4) NC supplemented with 500 ppm of the enzyme. In the second experiment, chickens were fed PC or PC + enzyme 350 ppm and a digestibility balance was performed. The enzyme supplementation at 350 and 500 ppm significantly improved the overall feed conversion ratio in PC and NC diet, respectively (P < 0.01). Regarding footpad dermatitis score, animals fed NC + enzyme 500 ppm tended to present a lower value than animals fed NC (P < 0.1). Concerning the digestibility balance, PC + enzyme 350 ppm diet presented a higher feed AME and AMEn value than PC diet (P < 0.05). The enzyme also improved the apparent ileal digestibility (AID) of proline (P < 0.05) and tended to increase AID of cysteine (P < 0.1). In conclusion, the enzyme preparation improves birds feed efficiency by increasing energy utilization.